2020
DOI: 10.1177/0883073820924147
|View full text |Cite
|
Sign up to set email alerts
|

Tumefactive Demyelinating Lesions in Children: A Rare Case of Conus Medullaris Involvement and Systematic Review of the Literature

Abstract: Tumefactive demyelinating lesions are an uncommon manifestation of demyelinating disease that mimic primary central nervous system neoplasms and can pose a diagnostic challenge in patients without a pre-existing diagnosis of multiple sclerosis. Although a biopsy may be required to distinguish TDL from neoplasms or infection, certain ancillary and radiographic findings may preclude the need for invasive diagnostic procedures. We describe the case of a 15-year-old boy with a tumefactive demyelinating lesion invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A recent review yielded only 79 published cases with tumefactive demyelinating lesions. 3 The most frequent childhood demyelinating disorders, MS, neuromyelitis optica spectrum disorders, and ADEM, typically present with multifocal lesions. Because both MLD (1 per 100,000 live births in Europe) and tumefactive lesions are extremely rare, it seems unlikely that the co-occurrence is a coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review yielded only 79 published cases with tumefactive demyelinating lesions. 3 The most frequent childhood demyelinating disorders, MS, neuromyelitis optica spectrum disorders, and ADEM, typically present with multifocal lesions. Because both MLD (1 per 100,000 live births in Europe) and tumefactive lesions are extremely rare, it seems unlikely that the co-occurrence is a coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…The term TD is defined radiologically as pseudo‐tumoral demyelinating lesions greater than 2 cm or lesions between 0.5 and 2 cm with possible mass effect 9 . There are 79 reported cases of TD in children till date and none in the posttransplant setting 2 . Some characteristic features that can be noted in these cases are rapid progression of symptoms over a short time period (<1 week), 4 involvement of multiple CNS sites, 5 white matter predilection, smaller mass effect than expected when considering the lesion size, and rapid improvement in MRI appearance with steroid 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The common IMDD post HSCT include acute disseminated encephalomyelitis (ADEM), Guillain–Barré syndrome (GBS), and chronic idiopathic demyelinating polyneuropathy (CIDP) 1 . Tumefactive demyelination (TD) is an unusual form of IMDD that has not been reported in the pediatric age group post HSCT 2 . The pathogenesis of this condition is uncertain, and it is debated whether the lesions result from autoimmunity or due to an allo‐reactive immune phenomenon in the spectrum of graft‐versus‐host disease (GVHD) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A careful history with emphasis on previous transient neurological signs not referable to a specific site in the CNS points to a diagnosis of MS.(2) In our case, prior to the onset of her motor deficit, the patient had been previously well, with no prior neurological symptoms. Pérez et al (3) found that headaches were the most common presenting complaint which although nonspecific in nature may point to a diagnosis of demyelination rather than neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…To date the literature on TDMS in children is scanty with only 79 published cases reported in the world literature (3) and as far as we are aware, this is the first reported case in South Africa. This small number of cases underscores the need for more awareness of the entity and in particular the awareness of the ability of neuroimaging to accurately diagnose these lesions without the need of histopathological confirmation.…”
Section: Introductionmentioning
confidence: 90%